Steward of resources - Abd Razak, Dzulkifli (2005)
Universiti Sains Malaysia (USM) has recently been designated as one of seven Regional Centres of Expertise by the United Nations University for its pioneering efforts to spearhead ideas for Education for Sustainable Development (ESD). USM ViceChancellor Professor Datuk Dzulkifli Abd Razak says the university has specifically been recognised as this year is marked by the United Nations as the beginning of the decade of BSD. "The focus is not about education in the context of just teaching students about ESD but more towards the need for doing something, making it work and applying ideas on sustainable development," Dzulkifli says. LUSH: USM University in a Garden makes a conducive environment for studies. "USM has long done substantial work towards translating the idea of sustainable development into something positive beginning with the implementation of the Kampus Sejahtera Programme (which can be roughly translated as Healthy Campus)."